Preparation and Evaluation of Paracetamol Effervescent Tablets under Normal and Exaggerated Storage Conditions (Bangladesh Pharmaceutical Journal, 2015)
A single blind study was conducted to prepare and evaluate paracetamol effervescent tablets. Potency, content uniformity, diameter, thickness and crushing strength of the prepared tablets were used as the bench mark parameters for quality assessment. Our results showed that all parameters met official values except for friability. The performance of the tablets in terms of duration of effervescence was investigated under high stresses of humidity as well as at low and high temperatures. The duration of the investigational period lasted for 3 days and results showed an increase in effervescence time in each case. In this study, the normal effervescence time at 111.00±14.22 seconds was changed to 286.13±55.18 seconds, 140.38±21.59 seconds and 158.63±26.14 seconds under high humidity, at refrigeration (representing cool temperature) and at high temperature, respectively. Here, a long term performance study was also conducted under normal storage conditions spanning a period of 60 days. Duration of effervescence on day 1 was 212.54±0.34 seconds, but at the end of 60 days the duration increased to 634.23±0.65 seconds. In the present study the changes in organoleptic properties were also evaluated. Results showed that the properties remained the same over a period of 60 days while the potency of the drug reduced from 99% to 95%. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22320 Bangladesh Pharmaceutical Journal 17(1): 75-78, 2014